Prevalence of low testosterone and its relationship to body mass index in older men with lower urinary tract symptoms associated with benign prostatic hyperplasia. (December 2013) - Kaplan, Steven A.; Lee, Jeannette Y.; O'Neill, Edward A.; Meehan, Alan G.; Kusek, John W.
Abstract Purpose: We examined the prevalence of low testosterone (LT) and its relationship with body mass index (BMI) in men with lower urinary tract symptoms (LUTS) associated with benign prostatic hyperplasia (BPH), who were enrolled in a clinical trial of drug therapy, the Medical Therapy of Prostatic Symptoms (MTOPS) Study. Materials and methods: MTOPS enrolled 3047 men, and of these, 1896 had total testosterone (TT) measured at baseline. LT was defined as a single measurement of TT of <300 ng/dL. Results: The overall prevalence of LT was 25.7%. Prevalence increased with increasing BMI; 14.7% among men who were normal weight (BMI <25 kg/m2) and 24.2% and 39.3% among overweight (BMI 25 to <30 kg/m2), and obese (baseline BMI ≥30 kg/m2) men, respectively. Conclusions: LT was observed in about one in four MTOPS study participants with baseline TT measurements. The prevalence of LT increased markedly with increasing BMI. Our findings suggest a high prevalence of LT in obese men with LUTS/BPH. Physicians should be alert to the possibility of symptoms of hypogonadism in this population.